Malaysia Abridged SimSmoke model - towards achieving 2025 and 2045 smoking prevalence targets - Mohamed Nor, Norashidah; Ross, Hana; Bui, Wency Kher Thinng; Abdul Ghani, Judhiana; Hassan, Norayana; Baharom, Nizam (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Introduction: In respond to the World Health Assembly global NCD target of 30% reduction in the prevalence of adult tobacco use by 2025, Malaysian government called for lowering its smoking prevalence to 15% by 2025. In addition, moving towards the endgame target of less than 5% smoking prevalence in 2045. Methods: Malaysia Abridged SimSmoke model, a simulation model uses specific policy parameters, the most recent smoking prevalence, and population size for Malaysia is developed to estimates and access the impact of MPOWER policies in achieving the targets. Results: The 15% prevalence rate in 2025 can be achieved if the Malaysian government increase tobacco excise tax to 72% of the retail price, implement and enforce comprehensive smoke-free air policies, ban all forms of advertising/promotions and run intensive mass media campaigns. Such approach would reduce the number of smokers by about 2.6 million, averting almost 1.3 million premature deaths in the long term. The tobacco endgame target of less than 5% smoking prevalence by 2045 is achievable if the excise tax is further increased to 86.5% of the retail price while all other tobacco control policies are kept at the enhanced level. Conclusions: Both the targeted smoking prevalence are a realistic proposition if the proposed measures are fully implemented. It requires a whole government approach with the MOH as a leading agency driving the process. It is important to monitor both the compliance with the new measures and smoking prevalence to make sure that Malaysia is on track in achieving its targets.